2009
DOI: 10.1080/13576500802328613
|View full text |Cite
|
Sign up to set email alerts
|

Post unilateral lesion response biases modulate memory: Crossed double dissociation of hemispheric specialisations

Abstract: We propose that what appears to be hemispheric specialisation in the memory domain, as indexed by effects of unilateral brain lesions, is to a great extent explainable as response bias: left hemisphere lesions result in an omissive response bias or error pattern whereas right hemisphere lesions result in a commissive response bias or error pattern. To test this prediction a group of 40 non-confabulatory cases with a verbal and non-verbal retention deficit (hypomnesia), subsequent to a unilateral lesion, was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…This model proposes that the LH is specialised for encoding and the RH for retrieval. Not only are more and more fMRI refutations being published (Owen, 2003) but if the conceptors had exhaustively looked over the behavioural neurology literature they would have found the psychic tonus pattern, and they would have found only three cases of a pure retrieval deficit (retrograde amnesia) after a unilateral lesion, in the entire world literature*two of which had LH lesions (Braun et al, 2007c).…”
Section: Hemispheric Specialisation Of Error Patterns In Memory In Anmentioning
confidence: 99%
See 1 more Smart Citation
“…This model proposes that the LH is specialised for encoding and the RH for retrieval. Not only are more and more fMRI refutations being published (Owen, 2003) but if the conceptors had exhaustively looked over the behavioural neurology literature they would have found the psychic tonus pattern, and they would have found only three cases of a pure retrieval deficit (retrograde amnesia) after a unilateral lesion, in the entire world literature*two of which had LH lesions (Braun et al, 2007c).…”
Section: Hemispheric Specialisation Of Error Patterns In Memory In Anmentioning
confidence: 99%
“…This suggests that in mammals with intact callosi, lesions in one hemisphere can affect release of functions dominant in the other hemisphere. Braun, Delisle, Rouleau, Guimond, and Daigneault (2007c) compiled all the previously published cases of psychometrically confirmed global anterograde amnesia (verbal and non-verbal) resulting from a unilateral lesion. Amnesia, as operationalised with most psychometric tests, consists of errors of omission.…”
Section: Hemispheric Specialisation Of Error Patterns In Memory In Anmentioning
confidence: 99%
“…Whereas disturbances of limbic structures can lead to paranoia or delusions, patients with bvFTD with delusions have bilateral or predominant rightsided frontal atrophy [38,44], and other neurological patients with delusions have right hemisphere or bifrontal lesions [8]. Whereas amnestic states from bilateral hippocampal, mamillary body, or related injury can lead to momentary or provoked confabulations, most studies indicate that lesions in the VMPFC are sufficient for confabulation [2,5,16,53]. The posterior medial OFC may contribute to confabulations via an inability to suppress interference of thoughts or extinguish previous anticipations [14,15,25,41,46].…”
Section: Discussionmentioning
confidence: 99%
“…Braun's (2007) "energetics" model states that the hemispheres of the brain play opposite roles in the management of the body's energy (glucose and oxygen expenditure of the body as a whole) regardless of lobe, with the left hemisphere playing the dominant role (inferred from the greater right hemisphere lesion effects) [66]. Braun, Delisle, Rouleau, Guimond, and Daigneault (2009) proposed that the right hemisphere generally behaves like an energy conserver and the left like an energy expender, and that this translates into opposed response-biases of each hemisphere [14]. They further proposed and that the opposed response-biases of the hemispheres should be detectable in any type of mental operation (attention, perception, memory, executive function, etc.).…”
Section: Implications For a General Theory Of Hemispheric Specializationmentioning
confidence: 99%
“…In a review of single case reports in the literature, Braun, Delisle, Rouleau, Guimond, and Daigneault (2009) demonstrated that pathological commissiveness in memory retrieval (confabulation, paramnesia, false memory, memory laden hallucination) is more common after right hemisphere lesions, whereas pathological omissiveness (global amnesia) is more common in memory retrieval following left hemisphere lesions [14]. Some single and multiple case report studies have also described an extremely high prevalence of false recognition following a right frontal lesion [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%